2014
DOI: 10.7314/apjcp.2014.15.17.7213
|View full text |Cite
|
Sign up to set email alerts
|

IL28B rs12979860 Gene Polymorphism in Egyptian Patients with Chronic Liver Disease Infected with HCV

Abstract: Background: Egypt has one of the highest prevalences of hepatitis C virus (HCV) infection worldwide. Although the IL28B gene polymorphism has been shown to modify the course of chronic HCV infection, this has not been properly assessed in the Egyptian population. Materials and Methods: The IL28B rs12979860 single nucleotide polymorphism (SNP) was therefore examined in 256 HCV-infected Egyptian patients (group II) at different stages of disease progression and in 48 healthy volunteers (group I). Group II was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
5
4
1
Order By: Relevance
“…Overall, 67.5 % of the patients were genotype CT, 22.5 % were genotype CC, and 10 % were genotype TT. A previous study suggested that the frequencies of these IL28B genotypes in healthy controls in Egypt are CT (52.1 %), followed by CC (29.2 %) and TT (18.8 %), which are comparable to those observed in our study [40]. The NR genotyped group was distributed as 4 (20 %) CC, 13 (65 %) CT, and 3 (15 %) TT.…”
Section: Resultssupporting
confidence: 89%
“…Overall, 67.5 % of the patients were genotype CT, 22.5 % were genotype CC, and 10 % were genotype TT. A previous study suggested that the frequencies of these IL28B genotypes in healthy controls in Egypt are CT (52.1 %), followed by CC (29.2 %) and TT (18.8 %), which are comparable to those observed in our study [40]. The NR genotyped group was distributed as 4 (20 %) CC, 13 (65 %) CT, and 3 (15 %) TT.…”
Section: Resultssupporting
confidence: 89%
“…The results of this study revealed IL28B rs12979860 C T genotype as the commonest genotype (68.9 ) and is in agreement with previous studies done on Egyptian patients (19,(30)(31)(32), suggesting a possible role of this genotype in the transition of a normal hepatocyte into an abnormal one. This genotype distribution was suggested to be a consequence of environmental or ethnic variation (30,32).…”
Section: Discussionsupporting
confidence: 92%
“…FIB-4 was first described in HCV HIV co-infection, and later validated as an accurate marker for the diagnosis of fibrosis stages in patients with HCV mono-infection (17,40), particularly advanced fibrosis and cirrhosis. At different cut-off values the accuracy of FIB-4 approached 70 (41) with high sensitivity and moderate specificity (32). For predicting significant fibrosis, FIB-4 had an AUC value of 0.645, as reported by Alboraie et al (17).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, this is not unexpected due to different patterns of correlation between SNPs in patients from different ethnic origin. For rs12979860, two studies found a significant association with HCC and two did not . Additionally, one study found a significant association with cirrhosis, although most studies using cirrhosis or fibrosis as an outcome did not find an association.…”
Section: Resultsmentioning
confidence: 96%